A spin wave resonance study on reentrant Au77Fe23 films - (:unkn) unknown (ELSEVIER SCIENCE SA, 1997)
Thin films prepared by both flash and slow evaporation of the bulk Au77Fe23 alloy have been studied by electron spin resonance (ESR) technique at the temperature range between 77-300 K. A series of spin wave resonance (SWR) peaks were observed at all temperatures when the external dc magnetic field is applied along the directions Lying in a small angular interval with respect to the film normal. The classical spin wave model has been used to analyze the experimental data. The magnetic parameters, such as exchange stiffness constant, the effective bulk and the surface anisotropy energy parameters of the system have been derived as a function of temperature. While the easy plane surface anisotropy almost remains constant, considerable increments were found in the exchange parameter. the magnetization and the linewidth with decreasing temperature. The SWR linewidths for the films obtained by slow evaporation at higher substrate temperatures are noticeably smaller compared to those of the film prepared by flash evaporation technique. (C) 1997 Elsevier Science S.A.
Keywords: alloys; anisotropy; electron spin resonance (ESR); magnetic properties and measurements; AU-FE ALLOYS; SHORT-RANGE-ORDER; THIN-FILMS; NIMN FILMS; GLASS; BEHAVIOR; MICROSTRUCTURE; FERROMAGNETISM; COEXISTENCE